1993
DOI: 10.1029/93gl01891
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reaction of CH3O2 with ClO at 293 K

Abstract: The reaction of CH3O2 with ClO has been studied at 293 K using a flow reactor sampled by a mass spectrometer. Under conditions where [ClO] » [CH3O2], the CH3O2 decayed under pseudo‐first‐order conditions giving a rate coefficient of (1.9±0.4)×10−12 cm³ s−1. CH3OCl was detected as a reaction product. The implications of the measurements for the chemistry of the stratosphere are discussed briefly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 11 publications
5
33
0
Order By: Relevance
“…This allows the proper identification of this channel as the most important pathway, in agreement with the experimental evidence [2][3][4][5][6][7][8][9]. (b) The formation of methyl chlorate isomer as a reaction intermediate is found to be possible not only from the CH 3 OOClO isomerization [10] but also directly from the reactants through the newly determined transition state TS1 located at À2.3 kcal mol À1 .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This allows the proper identification of this channel as the most important pathway, in agreement with the experimental evidence [2][3][4][5][6][7][8][9]. (b) The formation of methyl chlorate isomer as a reaction intermediate is found to be possible not only from the CH 3 OOClO isomerization [10] but also directly from the reactants through the newly determined transition state TS1 located at À2.3 kcal mol À1 .…”
Section: Discussionsupporting
confidence: 71%
“…However, other thermodynamically accessible channels have been also considered and investigated in subsequent studies [4,9] CH 3 Reaction enthalpy values, DH 298 , are taken from Helleis et al [4] with those in parentheses from Daële et al [9]. Thus, later experimental measurements [4][5][6][7][8][9] were able to identify methyl hypochloride, CH 3 OCl, among the reaction products, indicating that channel (1b) may also be a potentially important pathway with a considerable branching ratio at the low temperatures prevalent in the polar winter and early springtime stratosphere. The large discrepancies however, observed in the measured rate constant values of channels (1a) and (1b) [9], have created severe uncertainties about the real significance of each pathway.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…3.3.3 The heterogeneous reaction CH 3 OCl þ HCl. Kenner et al (1993) and Crowley et al (1994) suggested that the heterogeneous reaction CH 3 OCl þ HCl ! CH 3 OH þ Cl 2 (R22) might take place in analogy with the heterogeneous reaction R2.…”
Section: Reaction Of Chmentioning
confidence: 99%
“…However, in the upper atmosphere the reactions with atomic oxygen are of importance6. CH 3 CH 2 OBr is recognized to play a significant role in several of the processes involved in stratospheric ozone depletion cycles7–10. Thus, numerous studies have been devoted to the theoretical and experimental investigation of the properties of these compounds11–17.…”
Section: Introductionmentioning
confidence: 99%